1986
DOI: 10.1007/bf00402770
|View full text |Cite
|
Sign up to set email alerts
|

N-Nitrosodiethanolamine is activated in the rat to an ultimate genotoxic metabolite by sulfotransferase

Abstract: Inhibition of sulfotransferase by 2,6-dichloro-4-nitrophenol (DCNP) has been found to completely abolish the genotoxic potential of N-nitrosodiethanolamine (NDELA) in rat liver as indicated by induction of DNA single strand breaks. The DNA strand breaking potential of N-nitroso-2-hydroxymorpholine (NHMOR), a metabolite of NDELA formed by alcohol dehydrogenase-mediated oxidation, was also almost quantitatively abolished. In contrast to these beta-hydroxylated nitrosamines, the effectiveness of N-nitrosodiethyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Sterzel and Eisenbrand have suggested that sulfation of NDELA may be an activation mechanism, since induction of single-strand breaks was abolished by a sulfotransferase inhibitor (28). NDELA sulfate could cause 2-hydroxyethylatio n of DNA according to the mechanism proposed by Michejda and coworkers (29).…”
Section: Discussionmentioning
confidence: 98%
“…Sterzel and Eisenbrand have suggested that sulfation of NDELA may be an activation mechanism, since induction of single-strand breaks was abolished by a sulfotransferase inhibitor (28). NDELA sulfate could cause 2-hydroxyethylatio n of DNA according to the mechanism proposed by Michejda and coworkers (29).…”
Section: Discussionmentioning
confidence: 98%
“…After metabolic activation it has been shown to induce DNA-SSB in vitro in the human lymphoblastoid cell line Namalva [15]. After oral NDELA-application to rats, DNA strand break formation was observed in the liver [15,25,26]. Moreover, using P450-2E1-transfected V79 cells, NDELA was found to be cytotoxic and mutagenic, reflecting the involvement of P450-2E1 in its bioactivation [27].…”
Section: Introductionmentioning
confidence: 96%
“…Airoldi () observed a correlation between the the extent of β-oxidation of NDELA, as measured by production of metabolites NHMOR and NHEG, and its carcinogenicity in four different animal species. Both NDELA and NHMOR are effective producers of DNA SSB in rat liver DNA ( ). The DNA SSB produced by NDELA or NHMOR are either blocked or significantly modulated by inhibitors of ADH, P450, sulfotransferase, and probably other enzymes ( ).…”
Section: Introductionmentioning
confidence: 99%
“…Both NDELA and NHMOR are effective producers of DNA SSB in rat liver DNA ( ). The DNA SSB produced by NDELA or NHMOR are either blocked or significantly modulated by inhibitors of ADH, P450, sulfotransferase, and probably other enzymes ( ). While the inhibitors used in these experiments are likely to have effected more than a single enzyme system, the experiments were indicative of and supportive of the β-oxidation path.…”
Section: Introductionmentioning
confidence: 99%